'I changed my strategy and looked for jobs on Gumtree': the ecological circumstances and international graduates' agency and strategies to navigate the Australian labour market. Issue 5 (4th July 2022) - Tran, Ly Thi; Phan, Huong Le Thanh; Tan, George; Rahimi, Mark
ABSTRACT: Despite a significant number of international graduates staying in the host countries on post-graduation visas, their experiences in gaining access to the host labour market are less documented. This article addresses this critical but under-researched topic. It discusses the ecological circumstances impacting international graduates' participation in the Australian host labour market, including the temporality of their visas, employers' concerns, constraints of the market, time issue and bargaining position. Drawing on agency theory, the study shows two forms of agency enacted by international graduates in navigating the host market: needs-response agency, entailing their choice of field, persistence, and early job-seeking, and agency as becoming, entailing their professional identity development to become more employable. The study found the following common strategies adopted by international graduates: proactively explaining their work rights to employers, using alternative job search channels, reskilling, evidencing their professional skills, undertaking internships, networking and creating jobs for themselves and other peers. The study offered fresh insights into international graduates' career adaptive behaviours, job-seeking skills and career management skills.